1988
DOI: 10.1159/000124924
|View full text |Cite
|
Sign up to set email alerts
|

Central Serotoninergic Stimulation by Fenfluramine Challenge Does Not Affect Plasma Thyrotropin-Stimulating Hormone Levels in Man

Abstract: Thyrotropin-stimulating hormone (TSH) and prolactin (PRL) responses to an acute oral challenge of fenfluramine (60 mg), a central serotoninergic (5-hydroxytryptamine) releasing/uptake inhibiting agent, were examined in 8 healthy males in order to assess the role of central serotoninergic stimulation in the release of TSH. Plasma PRL, but not TSH, was significantly elevated by fenfluramine. These data suggest that central serotoninergic activity does not play an important role in the physiologic release of plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…After stimulation with dl-FEN no change (Sulaiman et al, 1975;Casanuevaetal., 1984;Lewisand Sherman, 1985;Weizmann et al, 1988) or just a slight increase (Murialdo et al, 1979;Lopez-Ibor et al, 1988) in growth hormone (HGH) secretion in humans has been reported. Furthermore, Coccaro et al (1988) were unable to document any influence of dl-FEN on TSH secretion in healthy young males, indicating that central serotonergic activity does not play an important role in the physiologie release ofplasma TSH in this population.…”
Section: Introductionmentioning
confidence: 68%
“…After stimulation with dl-FEN no change (Sulaiman et al, 1975;Casanuevaetal., 1984;Lewisand Sherman, 1985;Weizmann et al, 1988) or just a slight increase (Murialdo et al, 1979;Lopez-Ibor et al, 1988) in growth hormone (HGH) secretion in humans has been reported. Furthermore, Coccaro et al (1988) were unable to document any influence of dl-FEN on TSH secretion in healthy young males, indicating that central serotonergic activity does not play an important role in the physiologie release ofplasma TSH in this population.…”
Section: Introductionmentioning
confidence: 68%
“…(46) concluded that d,l‐fenfluramine does not have a detectable effect on dopamine in men. Fenfluramine is administrated orally (60 mg d,l‐mixture, 30 mg d‐mixture) and appears to be well tolerated by healthy subjects (47).…”
Section: Dl‐fenfluraminementioning
confidence: 99%
“…Furthermore, serotonin appears to be involved in nyctohemeral TSH periodicity [31]. In man, several investigators failed to demonstrate a measurable influence of serotonin on basal TSH secretion [3, 4, 5, 32], whereas serotonin was able to stimulate pituitary TSH release in vitro [33]. We could not find an influence of serotonin on basal TSH secretion.…”
Section: Discussionmentioning
confidence: 54%
“…Several studies have addressed the role of serotonin on prolactin [1, 2], LH [1, 3, 4] and TSH [3, 4, 5] secretion in men and normal cycling women.…”
Section: Introductionmentioning
confidence: 99%